The Influence of Social Media Perception on Students’ Attitudes toward Cyberbullying - Jonas Mulia Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
Social media has become an integral part of students’ daily lives. However, its intensive use may influence perceptions and attitudes toward online behaviors, including cyberbullying. This study examines the influence of social media perception on students’ attitudes toward cyberbullying. Using a quantitative survey method, data were collected from 160 students of the Faculty of Computer and Communication at Kwik Kian Gie Institute of Business and Informatics using stratified random sampling. A simple linear regression test showed a significant positive influence of social media perception on attitudes toward cyberbullying (Sig. = 0.001). The regression model Y = 33.559 + 0.176X indicates that increased perception scores are associated with stronger attitudes toward rejecting cyberbullying. The coefficient of determination (R² = 0.886) shows that 88.6% of the variance in attitudes toward cyberbullying is explained by social media perception. These findings highlight the need to strengthen digital literacy and ethical awareness among students.